Parenting adjustment through the process of parental divorce during the COVID-19 pandemic - Lawson Tettevie, Francisca (Kansas State University, 2023)
Using a Multi-System Model of Resilience framework (Liu et al., 2017, 2020), this study sought to synthesize the parenting adjustments divorced parents made and the resources they found helpful in fostering their children’s resilience. Interviews from 11 participants in the Coparenting Through a Pandemic project were used for this study. Participants were divorced parents who had completed a divorce education program and associated surveys between January 2020 and December 2021. Findings from this study were reported using three major identified themes: (a) parental adjustment and well-being, (b) parenting strategies, and (c) external sources of support for parents. Participants’ responses revealed their own adjustment to the divorce process and pandemic. Even though the COVID-19 pandemic may have exacerbated the stressors from the divorce process, parents described efforts taken toward helping their children simultaneously adjust to these multiple contexts and their inherent transitions. Participants elaborated on the different strategies they adopted and resources they found helpful in supporting their children. The findings of this study shed light on strategies to enhance the support provided by professionals working with divorced parents and divorce education programs, aiming to better serve families going through divorce in this ‘new normal.’
Keywords: COVID-pandemic; Divorce; Child adjustment; Resilience